Underdiagnosed Pulmonary Artery Thrombosis and Pulmonary Embolism in Rheumatic Heart Disease - Pu, Lei; Zhang, Yingjie; Li, Yaxiong; Yang, Yingnan (Cardiology and Cardiovascular Medicine, 2019)
Pulmonary embolism is a life-threatening acute cardiovascular disease and not easy to make an immediate diagnosis in clinical arena. A 46-year-old female with underdiagnosed pulmonary artery thrombus and pulmonary embolism in rheumatic heart disease, the patient’s presentation, diagnostic procedure and successful treatment are presented.